TEKSTUALITAS VIS-Ã€-VIS KONTEKSTUALITAS (STUDI KRITIS PENAFSIRAN AYAT-AYAT POLITIK MUHAMMAD ASAD [1900-1992]) - ASROOR, ZAIMUL (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
Muhammad Asad, one of the interpreters in the modern age from the West, is known as a figure whose views are quite progressive and contextual. However, there is little research that shows that in some of cases-Asad?s views also tend to be textual. This paper wants to show where the textuality and contextual interpretations of Muhammad Asad are, especially in some Islamic political matters. For instance, issues of Democracy and Shura, non-Muslim leaders and Jinayat Law. To analyze the above problems, the writer uses primary data in the form of his interpretation of The Message of the Qur?an and The Principle of State and Government in Islam. The method that the writer use is a comparative method with historical analysis and textual-contextual approach initiated by Abdullah Saeed